Zimbabwe women get together - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
The Zimbabwe Women's Bureau is an NGO association whose aim is to assist local groups in their efforts towards development. For 1989 its work will focus on <<building the future>>. The Zimbabwe Women's Bureau issues a newsletter which contains...